2019
DOI: 10.1038/s41433-019-0409-z
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral advanced (group D or E) intraocular retinoblastoma: outcomes in 72 Asian Indian patients

Abstract: Purpose To study the clinical presentation, treatment, and outcomes of patients with bilateral advanced intraocular retinoblastoma. Methods Retrospective case series of 72 patients. Results The mean age at presentation was 19 months. Leukocoria (n = 49, 68%) was the most common presenting complaint. The tumors were classified as groups D (n = 60, 42%) or E (n = 84, 58%) based on the Philadelphia version of International Classification of Retinoblastoma (ICRB); groups D (n = 84, 58%) or E (n = 60, 42%) based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 26 publications
1
15
0
1
Order By: Relevance
“…[ 24 25 ] In a study by Kaliki et al . [ 26 ] from India, systemic chemotherapy was the most commonly used primary treatment modality in view of advanced disease. In an attempt to salvage the eye and improve results for advanced disease neoadjuvant chemotherapy was offered to 87.5% patients in our analysis but it failed to help in preservation of the eye.…”
Section: Discussionmentioning
confidence: 99%
“…[ 24 25 ] In a study by Kaliki et al . [ 26 ] from India, systemic chemotherapy was the most commonly used primary treatment modality in view of advanced disease. In an attempt to salvage the eye and improve results for advanced disease neoadjuvant chemotherapy was offered to 87.5% patients in our analysis but it failed to help in preservation of the eye.…”
Section: Discussionmentioning
confidence: 99%
“…The globe survival rate was 47% [ 110 ] for bilateral group D eyes treated with systemic chemotherapy alone and increased to 68% in combination with low-dose intensity-modulated radiation therapy [ 119 ]. Group E eyes are often considered unsalvageable because of the metastatic risk [ 110 ], although multimodality treatment lead to less enucleation [ 9 ].…”
Section: Treatmentsmentioning
confidence: 99%
“…Studies have demonstrated that globes can be saved without an increased risk of metastatic disease or orbital recurrence by systemic chemoreduction and subsequent enucleation for poor responses [ 8 , 145 ]. Globe salvage can be achieved for advanced group D and E eyes with a lower rate for group E eyes, while some studies report vision salvage [ 9 , 134 , 138 , 151 ]. Clinical indications are needed to predict whether these high-risk pathological features present without histopathological examination, so that the globe can be spared or treated promptly.…”
Section: Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Тенденция к расширению показаний для комбинированного органосохраняющего лечения поддерживается большинством специалистов [15,30,31]. Показано, что применение локальной химиотерапии при РБ групп C-D не увеличивает количество рецидивов и частоту смертности от метастатической болезни [15,32,33].…”
Section: результатыunclassified